The Rolling-Up of Oligophenylenes to Nanographenes by a HF-Zipping Approach - Steiner, Ann-Kristin; Amsharov, Konstantin (Angewandte Chemie International Edition, 2017)
Intramolecular aryl–aryl coupling is the key transformation in the rational synthesis of nanographenes and nanoribbons. In this respect the C−F bond activation was shown to be a versatile alternative enabling the synthesis of several unique carbon-based nanostructures. Herein we describe an unprecedentedly challenging transformation showing that the C−F bond activation by aluminum oxide allows highly effective domino-like C−C bond formation. Despite the flexible nature of oligophenylene-based precursors efficient regioselective zipping to the target nanostructures was achieved. We show that fluorine positions in the precursor structure unambiguously dictate the “running of the zipping-program” which results in rolling-up of linear oligophenylene chains around phenyl moieties yielding target nanographenes. The high efficiency of zipping makes this approach attractive for the synthesis of unsubstituted nanographenes which are difficult to obtain in pure form by other methods.
CRIS-Team Scopus Importer:2022-04-14
Keywords: aryl–aryl coupling; C−F activation; domino reactions; nanographenes